The Influence of Family Adversities on Longitudinal Changes in Physical Inactivity Among Korean Adolescents During the COVID-19 Pandemic - Tae Kyoung Lee; Jing Zhu; Young Mi Kim; Ze-Kai Jiang; Meilin Zhang; Won Ha Choi; Tae-Young Pak; Hana Song (Korean Society for Preventive Medicine, 2024)
Objectives: Lack of physical activity has a critical effect on the physical and mental health of adolescents. This study examined the influence of family adversities on the longitudinal changes in physical inactivity among adolescents during the coronavirus disease 2019 (COVID-19) pandemic. Methods: The study used multi-wave data from the Korean Children and Youth Panel Survey, including 2590 Korean adolescents aged 12-14 years. The longitudinal trajectory of physical inactivity among adolescents and the effects of related factors were estimated using a latent growth modeling method. Results: Our results revealed a significant increase in physical inactivity among adolescents over time. At the onset of the pandemic, approximately one-seventh of Korean middle schoolers reported a lack of physical activity. However, 3 years later, during the quarantine, nearly one-fifth of these adolescents reported a significant increase in their physical inactivity. Initially, low level parental education was predictive of adolescents' physical inactivity, but this effect diminished over time, becoming statistically insignificant by the end of the 3-year period. Moreover, the increase in physical inactivity over the 3 years was significantly influenced by parental rejection. Conclusions: These findings suggest that adolescents who experience parental rejection are more likely to report an increase in sedentary behaviors in contexts such as the COVID-19 pandemic.